ISOLASI NON-DESTRUKTIF DAN DESTRUKTIF GEN COI PADA SERANGGA JENIS COLEOPTERA PEMBAWA PATOGEN CERATOCYSTIS - Anindya Safita Ningtias; Istiana Prihatini; Maryatul Qiptiyah (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2021)
Identification of insect species using molecular approach is one of the first steps in managing Ceratocystis. Proper species identification of the vectorsof Ceratocystiswill provide an effective way in limiting the distribution of this pathogenic fungi. The isolation of insect DNA is a crucial step in species identification using molecular characters. The aim of this research was to obtain the most effective method for isolating the COI gene and to confirm the insect DNA using amplification of the DNA through polymerase chain reaction (PCR). Twelve unidentified Coleoptera specimen collected from Acacia spp. plantation in Pelalawan Riau were randomly selected for this study. The insect DNA were isolated using the CTAB buffer with four different preincubation treatments, involved a non destructive method, i.e. soaking (R), destructive methods, i.e. crushing (H), soaking-crushing (RH) and freezing-crushing (FH). Two sets of primer, LCO1490/HCO2196 and LCO1490/HCO2198 were used to amplify the DNA of COI gene. The results shows, the COI gene was isolated from all pre-incubation treatments, except in the non-destructive treatment. The isolated DNA of COI gene was successfully amplified using both primer sets used in this study.